The Analysis of Fraudulent Financial Reports Through Fraud Hexagon on Public Mining Companies - Wicaksono, Agung; Suryandari, Dhini (Accounting Analysis Journal, 2021)
This research with a purpose to verify the effect of financial targets, financial stability, external pressure, supervision effectiveness, external auditor quality, change of auditors, CEO education, CEO duality, state-owned enterprises, political connections on the fraudulent financial report through hexagon fraud theory. Mining sector companies that registered on the Indonesia Stock Exchange in the period of 2017-2019 are the population in this research. The purposive sampling technique is used to select the research sample so as obtain samples of 41 companies and 123 analysis units. Panel regression analysis is an analytical technique that used in this research. The result shows that financial targets and external pressures have positive and significant effects on fraudulent financial reports. Meanwhile, financial stability, supervision effectiveness, external auditor quality, change of auditors, CEO education, CEO duality, state-owned enterprises, and political connections do not affect the fraudulent financial report. This research deduces that the higher financial targets and external pressures in a company make the possibility of management as an agent to commit fraudulent financial reports in order to attract investors will be more vulnerable. Kata Kunci: Fraud Hexagon Theory; Fraudulent Financial Report; F-Score Model